2010
DOI: 10.1111/j.1460-9568.2010.07420.x
|View full text |Cite
|
Sign up to set email alerts
|

Central thalamic deep brain stimulation for cognitive neuromodulation – a review of proposed mechanisms and investigational studies

Abstract: We review the history of efforts to apply central thalamic deep brain stimulation (CT/DBS) to restore consciousness in patients in coma and vegetative state by changing the arousal state. Early experimental and clinical studies and the results of a recent single-subject human study that demonstrated both immediate behavioral facilitation and carry-over effects of CT/DBS are reviewed. We consider possible mechanisms underlying CT/DBS effects on cognitively-mediated behaviors in conscious patients in light of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 65 publications
1
64
0
Order By: Relevance
“…Synchronous activity of thalamus and sensorimotor/insular cortices could therefore also be a result of both regions receiving similar input from another brain region, or being connected via that other region. However, other studies have shown significant decreases in brain arousal associated with central thalamic injury and significant deafferentation of its neurons due to diffuse brain insults in humans (Schiff and Plum, 2000;Shah and Schiff, 2010). Furthermore, sevoflurane-induced unconsciousness has been reversed by microinjection of nicotine, a cholinergic agonist, into the rat central thalamus (Alkire et al, 2007).…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…Synchronous activity of thalamus and sensorimotor/insular cortices could therefore also be a result of both regions receiving similar input from another brain region, or being connected via that other region. However, other studies have shown significant decreases in brain arousal associated with central thalamic injury and significant deafferentation of its neurons due to diffuse brain insults in humans (Schiff and Plum, 2000;Shah and Schiff, 2010). Furthermore, sevoflurane-induced unconsciousness has been reversed by microinjection of nicotine, a cholinergic agonist, into the rat central thalamus (Alkire et al, 2007).…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…One question, for example, is whether MD function is enhanced by enrichment in the presence of an ATN lesion. Other work has shown that low levels of thalamic stimulation can enhance conditional discrimination, which may provide additional tools for cognitive neuro-rehabilitation (Mair and Hembrook, 2008;Mair et al, 2011;Shah and Schiff, 2012). Savage and her colleagues have already produced novel evidence of recovery of function in PTD model of the Wernicke-Korsakoff syndrome.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…Specifically, with DBS the patient regained the ability to follow verbal commands, purposively manipulate objects, intelligibly communicate, and orally consume food (Schiff et al 2007). Regarding possible mechanisms for these effects, Shah and Schiff (2010) suggested that the central thalamus is instrumental in the transfer of arousalrelated information to the forebrain which is critical for maintaining requisite levels of cortical activation for effective cognitive functioning. In effect, DBS of intact regions of the midline thalamus serves to 'reactivate' previously dormant regions of cortex to restore levels of consciousness necessary for purposeful behavior.…”
Section: Functional Considerationsmentioning
confidence: 98%